PENGARUH SISTEM PENJAMINAN MUTU INTERNAL DAN SISTEM MANAJEMEN MUTU ISO 9001:2008 TERHADAP KINERJA ORGANISASI - Siska Willy (Universitas Muhammadiyah Semarang, 2018)
The government has issued various policies and regulations to improve the quality of higher education in Indonesia. National Education System Law (Undang-undang) No. 20 of 2003 explains that education evaluation consists of controlling activities, guarantees, and determining the quality of education must be carried out, both on study programs and educational institutions in a sustainable manner. Ministry of National Education, in this case the Higher Education requires that to graduate students, higher education must be accredited by the National Accreditation Board of Higher Education (BANPT). Thus, the higher education quality assurance system (SPM-PT) which is acceptable and applicable becomes a necessity to be fulfilled by the institution. In the current era of globalization and free trade, universities are competing to improve the quality of their education. this study uses survey explanatory methods. The results obtained are that there is a positive influence in this research, In addition to continuing to encourage universities to develop internal quality assurance systems, the government also continues to encourage universities to adopt ISO 9001 standards in the processes that take place in universities. This is done by the government so that universities can produce superior education services and produce graduates with good quality in accordance with international standards that apply. Keywords: Internal Quality Assurance System, ISO, Organizational Performance